2022
DOI: 10.3897/mbmg.6.78871
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-destructive DNA extraction protocols for insect metabarcoding: gentler and shorter is better

Abstract: DNA metabarcoding can accelerate research on insect diversity, as it is cheap and fast compared to manual sorting and identification. Most metabarcoding protocols require homogenisation of the sample, preventing further work on the specimens. Mild digestion of the tissue by incubation in a lysis buffer has been proposed as an alternative, and, although some mild lysis protocols have already been presented, they have so far not been evaluated against each other. Here, we analyse how two mild lysis buffers (one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Overall, our findings are in line with the results of Marquina et al (2022), who found that small and soft species were more difficult to detect after treatment with a chemically more aggressive buffer (higher SDS, DTT, and proteinase K concentrations) than after lysis with the milder buffer corresponding to Buffer 1 in the current study. They also agree with the results of Marquina et al (2019), who showed that hard-bodied and large insects are more easily detected in homogenates, while analysis of preservative ethanol – similar to extremely mild lysis – is better for the detection of small and soft-bodied insects.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, our findings are in line with the results of Marquina et al (2022), who found that small and soft species were more difficult to detect after treatment with a chemically more aggressive buffer (higher SDS, DTT, and proteinase K concentrations) than after lysis with the milder buffer corresponding to Buffer 1 in the current study. They also agree with the results of Marquina et al (2019), who showed that hard-bodied and large insects are more easily detected in homogenates, while analysis of preservative ethanol – similar to extremely mild lysis – is better for the detection of small and soft-bodied insects.…”
Section: Discussionsupporting
confidence: 93%
“…Our method is rapid, cost-effective, suitable for bulk samples and is gentle on specimens. Crucially, we were able to isolate sufficient DNA for many downstream molecular applications without addition of proteinase K or chemical lysis reagents which are common components in many published non-destructive methods [ 22 , 33 , 34 ] and are cost-prohibitive for large scale bulk sample processing. Another consideration that we felt crucial was to reduce physical damage to specimens by decreasing the processing time and minimising sample handling.…”
Section: Discussionmentioning
confidence: 99%
“…A striking subject of today's (and the future's) research concerns the advancing methodology of non‐destructive DNA extractions. Numerous studies dedicated to the development of non‐destructive methodologies for sequencing are emerging, showing that it is possible to extract DNA (although in smaller quantities) from specimens while keeping their structural integrity intact (Batovska et al, 2021; Carew et al, 2018; Kirse et al, 2022; Marquina et al, 2022; Martins et al, 2019; Martoni et al, 2022; Nielsen et al, 2019). Such protocols roughly consist of leaching DNA from whole individuals by temporarily submerging them in a digestive buffer (Castalanelli et al, 2010; Krosch & Cranston, 2012; Nielsen et al, 2019; Porco et al, 2010; Wong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such protocols roughly consist of leaching DNA from whole individuals by temporarily submerging them in a digestive buffer (Castalanelli et al, 2010; Krosch & Cranston, 2012; Nielsen et al, 2019; Porco et al, 2010; Wong et al, 2014). While various studies have tested non‐destructive DNA extractions on single arthropod specimens or samples of mock communities (see Castalanelli et al, 2010; Marquina et al, 2022; Nielsen et al, 2019), we only found one study that did so on real‐life bulk samples of terrestrial arthropods from Malaise traps (see Kirse et al, 2022). Malaise traps are especially challenging to process as they can contain hundreds to thousands of individuals (Geiger et al, 2016), each displaying various degrees of sclerotisation, which require different incubation times for adequate non‐destructive DNA extraction (Elbrecht et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation